Atg1-mediated Atg11 phosphorylation is required for selective autophagy by regulating its association with receptor proteins. Issue 1 (2nd January 2023) - Yao, Weijing; Li, Yixing; Chen, Yingcong; Chen, Yuting; Xie, Yu; Ye, Miaojuan; Zhang, Ying; Chen, Xiangjun; Wu, Xiaoyong; Feng, Yuyao; Hong, Zhi; Wang, Yigang; et al.
ABSTRACT: Atg11 is an adaptor protein required for the induction of selective autophagy via receptor binding. However, our understanding of the molecular mechanisms by which it regulates selective autophagy remains incomplete. Here, we show that Atg11 is phosphorylated by Atg1. Rapamycin treatment or starvation conditions induced slower electrophoretic mobility of Atg11 in an Atg1 kinase activity-dependent manner. Through in vitro kinase assays combined with mutagenesis, we determined that Atg1 phosphorylates S949, S1057, and S1064 residues in CC4 domain of Atg11. Replacing the three residues with alanine suppressed the cleavage of selective autophagy substrates for the cytoplasm-to-vacuole targeting (Cvt) pathway, mitophagy, reticulophagy, and pexophagy. The Atg11 mutant was defective in binding to related selective autophagy receptors. These results demonstrate a previously unknown function of Atg1 in regulation of selective autophagy via Atg11 phosphorylation. Abbreviations : AMPK: AMP-activated protein kinase; ATG: autophagy-related; Cvt: cytoplasm-to-vacuole targeting; FUNDC1: FUN14 domain-containing protein 1; GFP: green fluorescent protein; MTOR: mechanistic target of rapamycin kinase; PAS: phagophore assembly site; PIK3C3: phosphatidylinositol 3-kinase catalytic subunit type 3; PRKAC/PKA: protein kinase cAMP-activated; SD-G: glucose starvation; SD-N: nitrogen starvation; ULK1: unc-51 like autophagy activating kinase 1; λ-PPase: lambda protein phosphatase.